2018
DOI: 10.1038/s41598-018-23679-7
|View full text |Cite
|
Sign up to set email alerts
|

Response of Aquatic Bacterial Communities to Hydraulic Fracturing in Northwestern Pennsylvania: A Five-Year Study

Abstract: Horizontal drilling and hydraulic fracturing extraction procedures have become increasingly present in Pennsylvania where the Marcellus Shale play is largely located. The potential for long-term environmental impacts to nearby headwater stream ecosystems and aquatic bacterial assemblages is still incompletely understood. Here, we perform high-throughput sequencing of the 16 S rRNA gene to characterize the bacterial community structure of water, sediment, and other environmental samples (n = 189) from 31 headwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 80 publications
3
28
1
Order By: Relevance
“…The lowest pH value in the study (5.0) was observed in spring 2017 at Sebring Branch of Mill Run (NWIS ID 01548770), a site in the lowest sDII category with no OG or historic mining activity in its watershed and with the lowest observed specific conductance (14.7 μS/cm), suggesting that the low pH is a function of local geology, hydrology, and/or precipitation. This contrasts the findings of Chen See et al (31), Trexler et al (32), and Ulrich et al (48), which suggested that changes in pH resulting from acids used in shale gas well completion were significantly related to shale gas development in a similar geologic setting.…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…The lowest pH value in the study (5.0) was observed in spring 2017 at Sebring Branch of Mill Run (NWIS ID 01548770), a site in the lowest sDII category with no OG or historic mining activity in its watershed and with the lowest observed specific conductance (14.7 μS/cm), suggesting that the low pH is a function of local geology, hydrology, and/or precipitation. This contrasts the findings of Chen See et al (31), Trexler et al (32), and Ulrich et al (48), which suggested that changes in pH resulting from acids used in shale gas well completion were significantly related to shale gas development in a similar geologic setting.…”
Section: Resultscontrasting
confidence: 80%
“…Forty physical and chemical parameters were measured for this study (SI Appendix, Table S5), and, of these, specific conductance (as a proxy for TDS) and dissolved Cl, Br, Ca, Na, Li, B, Ba, and Sr are known as useful geochemical tracers of produced water (24,25,28,29,76,77). The pH was measured as a potential indicator for acids used in shale gas well completion and for potential effects on microbial and macroinvertebrate communities (32,33,48,78).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples from the previous study were classified as HF+ or HF-, based on proximity to hydraulic fracturing. Sequence data from sediment samples from Ulrich et al (2018) and this study were merged and quality filtered at an average expected error of 0.5 and truncation length of 150 bp. All downstream steps for filtering, OTU clustering, and normalization were performed as described above.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the abiotic half-lives of DBNPA at pH 5, 7, and 9 are 67 days, 63 h, and 73 min, respectively (10). Conversely, low pH has been characteristic of HF-impacted streams (11, 12), which thus provide favorable conditions for the stability of DBNPA and its degradation products.…”
Section: Introductionmentioning
confidence: 99%